WORKSHOP TREATMENT OF POST SURGICAL HYPOTHERMIC PATIENTS WITH WARMING ELEMENTS ON NURSES IN POST SURGICAL RECOVERY ROOM GRANDMED LUBUK PAKAM HOSPITAL - Kardina Hayati; Syatriawati .; Pitriani .; Arfah May Syara (JURNAL PENGMAS KESTRA (JPK), 2022)
Surgical procedures have a risk that the integrity or integrity of the body is disturbed and can even cause a life threat to the patient. One of the most at risk was the occurrence of postoperative hypothermia. In the postoperative recovery room, almost all postoperative patients were hypothermic. Nurses in the postoperative room usually provide blankets to warm patients who are hypothermic. This action was less effective to help patients overcome hypothermia. Giving warm fluids was considered effective to help increase the patient's body temperature. This workshop aims to provide knowledge and training on the administration of intravenous fluid heating elements to increase hypothermic body temperature to nurses in the post-surgical recovery room at the Grandmed hospital Lubuk Pakam. The evaluation of this workshop activity was seen from the knowledge of nurses and nurses' skills. Nurses' knowledge and skills were assessed using a questionnaire sheet and pre and post test observations. The results of the workshop showed that as many as 95% of nurses experienced an increase in knowledge and skills in overcoming hypothermia in postoperative patients. This workshop was expected to be able to overcome the problem of hypothermia in postoperative patients and increase the knowledge and skills of nurses.